Professional Requirements for Secondary School Principals in The Light Of 21st Century Competencies - Thaher, Khaled (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
The research aimed to identifying the professional requirements of secondary school principals in the light of the competencies of the 21st century. The researcher used the descriptive method using the survey method because of its suitability to the nature of the research. The research sample was deliberately selected from technical instructors and secondary school teachers in some general education schools in the State of Kuwait. The sample reached (94) individuals. The researcher concluded that the professional requirements of high school principals must keep pace with the developments of the educational process in light of the competencies of the twenty-first century, which are digital-age literacy skills, Inventive thinking skills, effective communication, and high productivity skills.